2016
DOI: 10.1099/ijsem.0.001406
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas turukhanskensis sp. nov., isolated from oil-contaminated soils

Abstract: A bacterial strain named IB1.1T was isolated in a screening of hydrocarbon-degrading bacteria from oil-contaminated soils on the territory of the Turukhansk District of Krasnoyarsk Krai, East Siberia, Russia. The 16S rRNA gene sequence had 98.7 % identity with respect to the closest phylogenetic relative, Pseudomonas granadensis F-278,770T, and the next most closely related species with 98.6 % similarity was Pseudomonaspunonensis, suggesting that IB1.1T should be classified within the genus Pseudomonas. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Their characteristics are presented in Tables 1 and 2. A description of the Pseudomonas turukhanskensis IB 1.1 strain was reported by Korshunova et al [25], while the P. plecoglossicida 2.4-D strain was described in the article by Chetverikov et al [34]. The presence of petroleum hydrocarbons in the soil is known to make mineral nutrients less accessible for plants [35].…”
Section: Properties Of Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristics are presented in Tables 1 and 2. A description of the Pseudomonas turukhanskensis IB 1.1 strain was reported by Korshunova et al [25], while the P. plecoglossicida 2.4-D strain was described in the article by Chetverikov et al [34]. The presence of petroleum hydrocarbons in the soil is known to make mineral nutrients less accessible for plants [35].…”
Section: Properties Of Microorganismsmentioning
confidence: 99%
“…For example, a model system consisting of bacteria (Sinorhizobium meliloti) capable of associative nitrogen fixation, hydrocarbon oxidation, and the production of auxins in combination with a grass (Sorghum bicolor) has been successfully used for the remediation of soils contaminated with polycyclic aromatic hydrocarbons [24]. Testing free living bacteria of Pseudomonas as hormone producers and plant growth promoters under conditions of contamination with petroleum is of no less interest than the study of associative bacteria, since the capacity for the active decomposition of hydrocarbons and resistance to adverse environmental conditions have been detected in many representatives of this genus [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…To establish precisely the phylogenetic affiliation of the novel isolates, in addition to the 16S rRNA gene sequence analysis, we also studied the three housekeeping genes more commonly used in the phylogenetic analysis of Pseudomonas species, rpoD, rpoB and gyrB genes [1,22,31,32,33,38,54]. The phylogenetic analysis of the concatenated rpoD, rpoB and gyrB genes sequences was performed with the same methodology as for the 16S rRNA gene and showed that the strains L10.10 T , A4R1.5 and A4R1.12 clustered in a separate branch related to a group formed by the type strains of the closely related species P. weihenstephanensis, P.…”
mentioning
confidence: 99%
“…Analysis of respiratory quinones of the novel strains showed the presence of Q9 (87%) and Q8 (10%). Q9 as the major ubiquinone of strains S1E40 T and S1E44 is consistent with Pseudomonas species [53, 54]. …”
Section: Resultsmentioning
confidence: 73%